2022
DOI: 10.1093/mnras/stac1824
|View full text |Cite
|
Sign up to set email alerts
|

A complex multiphase DLA associated with a compact group at z = 2.431 traces accretion, outflows, and tidal streams

Abstract: As part of our program to identify host galaxies of known z = 2–3 Mg ii absorbers with the Keck Cosmic Web Imager (KCWI), we discovered a compact group giving rise to a z = 2.431 DLA with ultrastrong Mg ii absorption in quasar field J234628+124859. The group consists of four star-forming galaxies within 8–28 kpc and v ∼ 40–340 km s−1 of each other, where tidal streams are weakly visible in deep HST imaging. The group geometric centre is D = 25 kpc from the quasar (D = 20–40 kpc for each galaxy). Galaxy G1 domi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 153 publications
0
2
0
Order By: Relevance
“…Gauthier (2013) have identified a z ∼ 0.5 galaxy group dominated by passive galaxies associated with a USMgii absorption system and argued that such strong absorption are driven by cool intragroup gas rather than star-formation-driven outflows. Nielsen et al (2022) have identified a compact galaxy group associated with a DLA, which is also a USMgii system at z ∼ 2.4, using KCWI and argued the gas in absorption is related to star-formation driven outflows, accretion from the IGM, and the tidal streams due to the galaxy-galaxy interactions. Some of the deviations shown by USMgii absorbers with respect to the relationships found for the general population of Mg ii absorbers could be explained if a good fraction of USMgii absorbers is not originating from the CGM of individual galaxies.…”
Section: Isolated Galaxy Vs a Group Of Galaxiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Gauthier (2013) have identified a z ∼ 0.5 galaxy group dominated by passive galaxies associated with a USMgii absorption system and argued that such strong absorption are driven by cool intragroup gas rather than star-formation-driven outflows. Nielsen et al (2022) have identified a compact galaxy group associated with a DLA, which is also a USMgii system at z ∼ 2.4, using KCWI and argued the gas in absorption is related to star-formation driven outflows, accretion from the IGM, and the tidal streams due to the galaxy-galaxy interactions. Some of the deviations shown by USMgii absorbers with respect to the relationships found for the general population of Mg ii absorbers could be explained if a good fraction of USMgii absorbers is not originating from the CGM of individual galaxies.…”
Section: Isolated Galaxy Vs a Group Of Galaxiesmentioning
confidence: 99%
“…For a fully saturated Mg ii line a 3Å limit on W2796 corresponds to a minimum velocity width of 320 kms −1 . Such large velocity spreads could be caused by (i) galactic-scale outflows (Nestor et al 2011a), (ii) filamentary accretion onto galaxies (Rubin et al 2012), and (iii) galaxy mergers (Rubin et al 2010) and intra-group gas (Gauthier 2013;Nielsen et al 2022;Zou et al 2018). In such instances, one could use the measured metallicities (Lehner et al 2013) and galaxy orientations relative to quasar sightlines to differentiate between the various possibilities (Kacprzak et al 2012).…”
Section: Introductionmentioning
confidence: 99%